Quality, reliability, security and robustness in heterogeneous systems : 14th EAI International Conference, Qshine 2018, Ho Chi Minh City, Vietnam, December 3-4, 2018, Proceedings /: 14th EAI International Conference, Qshine 2018, Ho Chi Minh City, Vietnam, December 3-4, 2018, Proceedings. (2019) - Unknown
No abstract available